2019
DOI: 10.1080/17461391.2019.1655098
|View full text |Cite
|
Sign up to set email alerts
|

The Placebo and Nocebo effect on sports performance: A systematic review

Abstract: The aim of this review was to determine the magnitude of the placebo and nocebo effect on sport performance. Articles published before March 2019 were located using Medline, Web of Science, PubMed, EBSCO, Science Direct, and Scopus. Studies that examined placebo and nocebo effects of an objective dependent variable on sports performance, which included a control or baseline condition, were included in the analysis. Studies were classified into two categories of ergogenic aids: 1) nutritional and 2) mechanical.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(139 citation statements)
references
References 73 publications
4
113
4
Order By: Relevance
“…Specific studies addressing the placebo effect of caffeine on cycling performance indicate the performance benefit is on the order of 1-3% (38). In a recent review of placebo effects associated with various nutritional ergogenic aids, Hurst et al (39) conclude the overall effects are small to moderate on exercise performance (Cohen's d ¼ 0.35). When considering placebos most relevant to this study, it was reported in 8 studies of caffeine and 5 studies of fictitious sport supplements that Cohen's d were 0.40 and 0.21, respectively (39).…”
Section: Discussionmentioning
confidence: 99%
“…Specific studies addressing the placebo effect of caffeine on cycling performance indicate the performance benefit is on the order of 1-3% (38). In a recent review of placebo effects associated with various nutritional ergogenic aids, Hurst et al (39) conclude the overall effects are small to moderate on exercise performance (Cohen's d ¼ 0.35). When considering placebos most relevant to this study, it was reported in 8 studies of caffeine and 5 studies of fictitious sport supplements that Cohen's d were 0.40 and 0.21, respectively (39).…”
Section: Discussionmentioning
confidence: 99%
“…Another barrier to adherence in people with chronic pain conditions can be pain exacerbation with exercise 35 . It is known that the motor performance can be bi‐directionally modulated by expectations, placebo and nocebo effects 36 . However, how expectations (positive or negative) and pain intensity interact with the nocebo and exercise intensity in PWH remains unknown and future studies are needed, particularly in those patients with high levels of pain.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst much research in sport describes positive effects on performance following a placebo treatment, most studies do not identify mechanisms. We may for example be confident given research findings that placebo caffeine might result in a 1-3% increase in endurance performance (Beedie & Foad, 2009;Hurst et al, 2019), but unsure as to precisely what physiological changes have facilitated that effect. Benedetti and co-workers (Benedetti et al, 2018) reported a series of studies investigating the effects of placebo oxygen (O 2 ) on cardiorespiratory, subjective and performance variables at high altitude.…”
Section: Physiological Responses To a Placebomentioning
confidence: 99%
“…Placebo effects appear to enhance sports performance. A recent systematic review identified 34 studies of the placebo and/or nocebo effect in sport involving 1,555 participants (Hurst et al, 2019). It reported small to moderate placebo effects for nutritional (d = 0.35) and mechanical (d = 0.47) ergogenic aids.…”
Section: How and Why Are Placebo And Nocebo Effects Relevant To Sportmentioning
confidence: 99%